Capital in the twenty-first century - Piketty, Thomas 1971- (Belknap Press of Harvard Univ. Press, 2014)
The main driver of inequality--returns on capital that exceed the rate of economic growth--is again threatening to generate extreme discontent and undermine democratic values. Thomas Piketty`s findings in this ambitious, original, rigorous work will transform debate and set the agenda for the next generation of thought about wealth and inequality.